Spindle cell lipoma of the tongue: First case report from the Gulf region and review of the literature - Ahmed Hafez Mousa; Houriah Yasir Nukaly; Rawan Elwalid Ali Mohamed; Nagam AlShehabi; Rabbani Mahmoud Daoud; Abdelrahman Waleed Alsayed; Ramla Mohamed Farah Roble; Nigar Mehtiyeva; Farah Ennab; Temaa Alklani; Islam Khaled (Clinical Case Reports, 2023)
Key Clinical Message Spindle cell lipoma is a histological variant of oral lipomas. In this report, we present the first case from the Gulf region with the most comprehensive literature review. Clinicians should consider rare tumors in the differential diagnoses of oral masses.